From Wealth to Power : The Unusual Origins of America's World Role - Zakaria, Fareed (Book collections on Project MUSE., 1999)
What turns rich nations into great powers? How do wealthy countries begin extending their influence abroad? These questions are vital to understanding one of the most important sources of instability in international politics: the emergence of a new power. In From Wealth to Power, Fareed Zakaria seeks to answer these questions by examining the most puzzling case of a rising power in modern history--that of the United States. If rich nations routinely become great powers, Zakaria asks, then how do we explain the strange inactivity of the United States in the late nineteenth century? B.